Effect of Home Exercise Program in Chronic Non-specific Low Back Pain - Tamizh Maran DJ,; Alagumoorthi G,; Viswanathan S, (The Bioscan, 2025)
Home Exercise Programme (HEP) is an alternative to supervised exercise therapy for patients with Chronic Non-Specific Low Back Pain (CNLBP). Complexity and burden of exercises were found to be important barriers related to adherence to HEP, affecting its effectiveness. This pilot study was conducted with 7 CNLBP patients to determine the safety, feasibility, adherence and effectiveness of a simple and graded HEP. The HEP consists of 6 exercises a day, for 5 days a week, for 6 weeks. The outcome measure includes semi-structured questionnaires for assessing feasibility, safety and adherence, Pain intensity, Functional abilities and Quality of Life, was taken at baseline, end of III and VI weeks. Statistical analysis was done by Kruskal Wallis ANOVA. No adverse events were reported and found feasible with 98.41% adherence. Significant improvement was observed in all the outcome measures with p < 0.05. This HEP is a safe, feasible and effective intervention for CNLBP.